Analisis kesalahan penggunaan kaidah kebahasaan dalam karangan deskripsi peserta didik kelas iv sekolah dasar - Afifah Martanti; Anesa Surya; Slamet Slamet (Universitas Sebelas Maret, 2022)
Abstract. This study aims to describe, (1) forms of spelling errors, (2) forms of diction errors, (3) forms of effective sentence errors, (4) forms of paragraph errors, (5) the most dominant errors, and (6) the cause of the incorrect use of the rules. language in the description of fourth grade students at SDN Tegalayu Surakarta. This research is a qualitative descriptive study. The subjects in this study were fourth grade students and fourth grade teachers. Data collection techniques used document studies, in-depth interviews, and unstructured observations. The validity test technique used is triangulation of sources and techniques. The data analysis technique used is Miles and Huberman interactive analysis. The results of this study are as follows. There are 60,14% spelling errors, 22,22% diction errors, 10,45% effective sentence errors, and 7,19% paragraph errors. The most dominant error is spelling error. Factors causing language errors caused by students include: (1) low vocabulary, (2) lack of knowledge, and (3) lack of motivation. While the teacher factor is the selection of learning strategies that are lacking and limited time. So that, teachers should choose the right learning media, improve simple writing activities, and literacy.